Assisted dying reframed in the context of English law's approach to suicide. (December 2020) - Wicks, Elizabeth
This article seeks to reframe the issue of assisted dying in terms of English law's broader regulation of suicide. It identifies a long-standing ambiguity about the role of the law in respect of suicide, notwithstanding its decriminalisation in the Suicide Act 1961. Reviewing the passage of that Act and subsequent judicial and parliamentary involvement, the article identifies some pertinent unanswered questions such as whether suicide can ever be viewed as a legitimate exercise of autonomy; whether assistance in performing suicide should ever be lawful; and when exactly there is a legal duty on others to intervene to prevent a suicide. It is argued that until such questions are addressed directly in the broader context of suicide, the appropriate legal approach to assisted dying cannot be settled.